Pemberian Bekam Terhadap Suhu Tubuh Mahasiswi Putri Ma’had Al-Jami’ah UIN Sulthan Thaha Saifuddin Jambi - Nur Asiah Esi (EDU-BIO: Jurnal Pendidikan Biologi, 2018)
This article discusses about the Influence of Cupping on Body temperature of female students at Ma'had Al-Jami'ah. This research is a quantitative research using Pre-Experimental Design and One-Group Pretest-Posttest Design. The sample in this research is female students of ma'had al-jami'ah numbering 30 people. Sampling was done by sampling purposive. With a cupping step those are a) temperature measurement before cupping b) Wet snow therapy 1 time intervention c) Measurement of Body Temperature After cupping. Research results obtained that between the body temperature before cupping and after the cupping there is a significant influence. This implies, the use of cupping can successfully lower the body temperature of female students of ma’had al-jami’ah significantly because this research uses negative correlation. Keyword: Cupping, Body temperaturve